SURVEI KINERJA KONEKSI INTERNET DAN KEMAMPUAN INVESTASI WARNET DI YOGYAKARTA - Krisnadewara, P. Didit (KINERJA, 2004)
This research tries to measure internet-services rental connection performance and the owner’s investment capacity in Yogyakarta. By conducting a field survey, the data obtained then is descriptively analyzed. The analysis shows that internet-services rental industry in Yogyakarta can be classified as small-scale internet services industry with only 1 to 20 unit of personal computers. In addition, the kind of connection used is the wireless 2.4 G.Hz. (54.29%) with a connection speed of 64 k.b.p.s. (51.43%). Most of the owner (45.05%) of the internet-services rentals are willing to increase their investment to upgrade the connection performance up to 10 millon rupiahs.Keywords: connection performance, investment capacity, internet, internet-services rental